1990
DOI: 10.1139/v90-097
|View full text |Cite
|
Sign up to set email alerts
|

The reaction of aluminum atoms with methane

Abstract: . Can. J. Chem. 68, 633 (1990). Ab initio SCF and CISD calculations with split valence and larger basis sets have been carried out for several possible reactions of ground state ( 2~) aluminum atoms with methane. In particular, the barriers to insertion of A1 into a CH bond to give a CH3AIH intermediate and the abstraction of a hydrogen by A1 to give AIH and CH3 have been studied. At the SCF level, transition state structures have been located and verified by vibrational analyses. In addition, intrinsic reacti… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
6
1

Year Published

1994
1994
2006
2006

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 14 publications
0
6
1
Order By: Relevance
“…As with the previously studied Al−H 2 complex, chemical reaction within the Al−CH 4 complex to yield electronically excited AlH(A 1 Π) products is energetically allowed. An additional chemical reaction pathway to form AlCH 3 products is possible for the Al−CH 4 complex . Unfortunately, fluorescence from electronically excited AlCH 3 has not, to our knowledge, been observed, although the laser spectroscopic detection of AlCH 3 by resonance-enhanced multiphoton ionization has been reported .…”
Section: Resultsmentioning
confidence: 92%
See 2 more Smart Citations
“…As with the previously studied Al−H 2 complex, chemical reaction within the Al−CH 4 complex to yield electronically excited AlH(A 1 Π) products is energetically allowed. An additional chemical reaction pathway to form AlCH 3 products is possible for the Al−CH 4 complex . Unfortunately, fluorescence from electronically excited AlCH 3 has not, to our knowledge, been observed, although the laser spectroscopic detection of AlCH 3 by resonance-enhanced multiphoton ionization has been reported .…”
Section: Resultsmentioning
confidence: 92%
“…The possible reaction pathways in this system have been investigated by quantum mechanical theoretical methods. 3 It was found that the lowest-energy CH 3 AlH product can be reached from the reaction of ground-state atoms with methane through a high-barrier insertion process.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…The reaction of bare atoms/clusters with compounds has been a very active field of research. As an important class of reactions, the insertion of bare atoms into molecules such as CH 4 , CH 3 -Hal, NH 3 , H 2 O, C 2 H 2 , and C 2 H 4 has interested scientists for many years. However, there has been less attention paid to the insertion of atom dimers/clusters, and there is little knowledge about the reactivities of atom dimers/clusters vs atoms. To our knowledge, although several experimental and theoretical studies 2,11,12 have indirectly shown that some atom dimers/clusters are more reactive than bare atoms, no direct and detailed experimental and theoretical evidence to prove it has been reported.…”
mentioning
confidence: 99%
“…There appears to have been no previous observations of HCuCl. However, there have been numerous experimental, and theoretical examples of metal atoms inserting into covalent bonds.…”
Section: Discussionmentioning
confidence: 99%